2008
DOI: 10.1136/ard.2008.090803
|View full text |Cite
|
Sign up to set email alerts
|

Definition of arthritis candidate risk genes by combining rat linkage-mapping results with human case-control association data

Abstract: High-resolution mapping in AIL populations defines limited sets of candidate risk genes, some of which appear also to associate with RA and thus may give clues to evolutionarily conserved pathways that lead to arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…There is in fact evidence that loci close to APLEC can regulate both arthritis and encephalomyelitis. 36,37 Nonetheless, the recent report that deletion of mouse Dcir1 influences arthritis and autoimmunity, 38 combined with our similar results regarding rat APLEC 5,6 and the association of RA with human APLEC and DCIR, 6 do point to evolutionarily conserved functions.…”
Section: Discussionsupporting
confidence: 68%
“…There is in fact evidence that loci close to APLEC can regulate both arthritis and encephalomyelitis. 36,37 Nonetheless, the recent report that deletion of mouse Dcir1 influences arthritis and autoimmunity, 38 combined with our similar results regarding rat APLEC 5,6 and the association of RA with human APLEC and DCIR, 6 do point to evolutionarily conserved functions.…”
Section: Discussionsupporting
confidence: 68%
“…This was consistent with other microarray results in experimental mice model [40]. Backdahl et al [41], recently reported that Clec4a1 was a candidate gene in inflammatory disease such as rheumatoid arthritis. Mafb is one of transcription factors involved during macrophage differentiation and/or inflammatory response [42].…”
Section: Discussionsupporting
confidence: 86%
“…In experimental arthritis a QTL has been identified in both DA/PVG and DA/F344 crosses on chromosome 10 [14, 50, 60]. This arthritis specific QTL was fine-mapped in pristine-induced arthritis using an AIL G10 [14].…”
Section: Resultsmentioning
confidence: 99%
“…The influence of genomic variations on the development of inflammatory disease by different genomes and MHC haplotypes. The illustration is an adaptation from [14]. …”
Section: Introductionmentioning
confidence: 99%